Effect of 1‐ and 2‐Month High‐Dose Alpha‐Linolenic Acid Treatment on 13C‐Labeled Alpha‐Linolenic Acid Incorporation and Conversion in Healthy Subjects. Issue 20 (19th September 2018) - Pignitter, Marc; Lindenmeier, Michael; Andersen, Gaby; Herrfurth, Cornelia; Beermann, Christopher; Schmitt, Joachim J.; Feussner, Ivo; Fulda, Martin; Somoza, Veronika
Abstract : Scope: The study aims at identifying 1) the most sensitive compartment among plasma phospholipids, erythrocytes, and LDL for studying alpha‐linolenic acid (ALA) conversion, and 2) whether ALA incorporation and conversion is saturable after administration of 13 C‐labeled ALA‐rich linseed oil (LO). The effect of a daily intake of 7 g nonlabeled LO (>43% w/w ALA) for 1 month after bolus administration of 7 g 13 C‐labeled LO on day 1, and for 2 months after bolus administration of 7 g 13 C‐labeled LO on day 1 and day 29 on 13 C‐ALA incorporation and conversion into its higher homologs is investigated in healthy volunteers. Methods and results: Incorporation and conversion of LO‐derived 13 C‐labeled ALA is quantified by applying compartmental modeling. After bolus administration, a fractional conversion of approximately 30% from 13 C‐ALA to 13 C‐DHA is calculated as reflected by the LDL compartment. Treatment with LO for 8 weeks induces a mean reduction of 13 C‐ALA conversion to 13 C‐DHA by 48% as reflected by the LDL compartment, and a mean reduction of the 13 C‐ALA incorporation into LDL by 46%. Conclusion: A 2‐month dietary intake of a high dose of LO is sufficient to reach saturation of ALA incorporation into LDL particles, which are responsible for ALA distribution in the body. Abstract : 13 C‐labeled linseed oil (LO) is used to study the incorporation and conversion of alpha‐linolenic acid in healthy subjects. LDL is identified as the most sensitive compartment compared to plasma phospholipids and erythrocytes to study alpha‐linolenic acid conversion to docosahexaenoic acid. Compartmental modeling reveals a fractional conversion of 30% from 13 C‐alpha‐linolenic acid to 13 C‐docosahexaenoic acid. Long‐term intake of LO markedly reduces the incorporation of 13 C‐alpha‐linolenic acid by 46% and its conversion to 13 C‐docosahexaenoic acid by 48%.